Divertículo congênito do ventrículo esquerdo associado a defeitos da parede tóraco-abdominal: relato de paciente operada em idade adulta Muscular diverticulum of the left ventricle associated with anomalies of the abdominal wall: report of an adult patient operated on - Roney Ronald Peixoto da Silva (Brazilian Journal of Cardiovascular Surgery, 1992)
O divertículo congênito do ventrículo esquerdo é anomalia rara. Pode estar associado a defeitos da parede tóraco-abdominal e a lesões intracardíacas. Quando isto ocorre, recebe o nome de síndrome de Cantrell. É relatado o caso de paciente de 25 anos de idade submetida a tratamento cirúrgico. Muscular diverticulum of the left ventricle is a rare anomaly. It is frequently associated with other congenital anomalies of the abdominal wall, sternum, diaphragm, pericardium and the heart itself. These have been described as Cantrell syndrome. This paper reports a case of a 25-year-old female patient submitted to surgical repair of this syndrome.